Examining human–carnivore interactions using a socio-ecological framework: sympatric wild canids in India as a case study. Issue 5 (29th May 2019) - Srivathsa, Arjun; Puri, Mahi; Karanth, Krithi K.; Patel, Imran; Kumar, N. Samba
Abstract : Many carnivores inhabit human-dominated landscapes outside protected reserves. Spatially explicit assessments of carnivore distributions and livestock depredation patterns in human-use landscapes are crucial for minimizing negative interactions and fostering coexistence between people and predators. India harbours 23% of the world's carnivore species that share space with 1.3 billion people in approximately 2.3% of the global land area. We examined carnivore distributions and human–carnivore interactions in a multi-use forest landscape in central India. We focused on five sympatric carnivore species: Indian grey wolf Canis lupus pallipes, dhole Cuon alpinus, Indian jackal Canis aureus indicus, Indian fox Vulpes bengalensis and striped hyena Hyaena hyaena . Carnivore occupancy ranged from 12% for dholes to 86% for jackals, mostly influenced by forests, open scrublands and terrain ruggedness. Livestock/poultry depredation probability in the landscape ranged from 21% for dholes to greater than 95% for jackals, influenced by land cover and livestock- or poultry-holding. The five species also showed high spatial overlap with free-ranging dogs, suggesting potential competitive interactions and disease risks, with consequences for human health and safety. Our study provides insights on factors that facilitate and impede co-occurrence between people and predators. Spatial prioritization of carnivore-rich areas and conflict-prone locations could facilitate human–carnivore coexistence in shared habitats. Our framework is ideally suited for making socio-ecological assessments of human–carnivore interactions in other multi-use landscapes and regions, worldwide.